Analisis Self Efficacy Siswa dalam Pembelajaran Matematika: Studi Kasus di SMA Negeri 1 Cigugur dengan Kurikulum Merdeka - Sukmawati, Reka Kurnia; Yusritawati, Ita; Salsabila, Sarah; Dewi, Metha Frisila; Wulandari, Inayah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Self-efficacy is a central belief in learning, especially mathematics learning, because it can have a strong influence on students' self-confidence. If students are in the high self-efficacy category, then they will be able to solve mathematical problems successfully. The aim of this research is to analyze students' sense of self-confidence or belief in their abilities. This research method is qualitative descriptive research with subjects in class X SMA. The analysis was carried out using Bandura's theory. There are three dimensions. Namely: dimensions of Magnitude (size), Strength (strength), and Generality (general). In general, a person's self-efficacy is not limited to certain situations. The results of this research analysis show that the overall level of student Self Efficacy is at a good level. This shows that students at SMA Negeri 1 Cigugur have a good level of persistence and perseverance when facing challenging and difficult mathematics assignments